2005
DOI: 10.1007/s10029-005-0342-x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of mesh and sutured repair for adult umbilical hernias

Abstract: Adult umbilical and paraumbilical hernia repair is associated with a high recurrence rate of 10-30%. Mesh repair has been reported to be associated with low recurrence rates. This study aims to compare sutured repair with prosthetic mesh repair to evaluate recurrence and infection rates. A retrospective study was conducted over an 8-year period including all the umbilical and paraumbilical hernia repairs performed by one consultant surgeon. The hernias were repaired using interrupted suture, Mayo overlap, flat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 14 publications
1
56
0
4
Order By: Relevance
“…Surgical repair using mesh is the current trend in the treatment of primary or recurrent umbilical hernias in both obese and non-obese adults due to its lower recurrence rate as compared to surgical repair by suturing (1% vs. 11%). [32,33] In conclusion, the present study demonstrated that advanced age (≥65 years), presence of concomitant disease, intestinal strangulation, necrosis and intestinal resection, high ASA score (III-IV), and time from onset of the symptoms were effective on morbidity and mortality. General anesthesia poses a risk for morbidity as well.…”
Section: Discussionmentioning
confidence: 51%
“…Surgical repair using mesh is the current trend in the treatment of primary or recurrent umbilical hernias in both obese and non-obese adults due to its lower recurrence rate as compared to surgical repair by suturing (1% vs. 11%). [32,33] In conclusion, the present study demonstrated that advanced age (≥65 years), presence of concomitant disease, intestinal strangulation, necrosis and intestinal resection, high ASA score (III-IV), and time from onset of the symptoms were effective on morbidity and mortality. General anesthesia poses a risk for morbidity as well.…”
Section: Discussionmentioning
confidence: 51%
“…[8][9][10] Recurrence is less seen in Mesh repair which is also evident from our study. [9][10][11][12] The mean surgical time is basically determined by the size of hernia and intraperitoneal adhesion formation and not essentially by the methods of reconstruction. [6,[13][14][15] We confirmed these observations when we found numerous difference between two groups (group 'A' and group 'B'), but there was no significant differences between the types of reconstructions inside these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cuando los índices de recidiva de ésta téc-nica son comparados con los de técnicas protésicas se observa que son significativamente más altos, no superando el 2% en éstas últimas 1,2,4 . Otros trabajos retrospectivos que comparan herniorrafias con hernioplastías informan 0% de recidivas con la utilización de mallas 14 .…”
Section: Discussionunclassified